Biofuels: Political/Economic Boondoggle or Energy Salvation for Western States? - Douglas L. Young (Journal of Agricultural and Resource Economics, 2009)
Nearly all western states lack comparative advantages for producing corn for ethanol and oilseeds for biodiesel. Despite this disadvantage, most western states have legislated incentives for production of biofuels. Unfavorable changes in price relationships, high transportation costs for imported feedstocks, and tight credit markets in 2008 and 2009 led to bankruptcies and plant closures at a disproportionate rate in the western biofuel industry. Policy makers in western states are advised to fund research and development for bioenergy and biofuel feedstocks in which they have a comparative advantage. These include forestry by-products, food processing and crop residues, and livestock wastes.